Advancing Digital Frontiers: Developing an AI-Driven Website for Enhanced User Experience and Efficiency - Wlasinsky , Oleg; Gromenskov, Tanya (TOPAZART, 2024)
This article explores the development of an AI-driven website, emphasizing the integration of artificial intelligence to enhance user experience, streamline operations, and improve overall efficiency. As digital landscapes evolve, the demand for intelligent and adaptive web solutions has surged, making AI a pivotal component in modern website development. This study examines the methodologies, tools, and technologies involved in creating an AI-based website, focusing on key aspects such as personalized content delivery, automated customer support, and data-driven decision-making. By leveraging AI, the website can dynamically adapt to user behavior, providing a more engaging and responsive experience. The research also addresses the challenges and considerations in implementing AI technologies, such as data privacy, algorithmic bias, and scalability. The findings suggest that incorporating AI into website development not only meets the growing expectations of users but also offers businesses significant competitive advantages in the digital marketplace. This study contributes to the field by providing a framework for developing AI-driven websites, highlighting best practices, and proposing future directions for research and development in this area.